E-076 Correlating wall shear stress and permeability of intracranial aneurysms. (22nd July 2018) - Pan, M; Vakil, P; Vali, A; Markl, M; Schnell, S; Ansari, S
Abstract : Purpose: Rupture risk assessment of intracranial aneurysms using non-invasive MRI is an active area of research, particularly in the realm of intra-aneurysmal flow modeling with 4D Flow MRI and imaging of wall tracer uptake and permeability using DCE-MRI. While several studies have examined these parameters independently, no study has thus far examined them simultaneously in the same patient. In this work we report the comparison of intra-aneurysmal hemodynamic parameters with wall permeability modeling within the same patient. Materials and methods: With IRB approval we acquired 4D Flow Phase-Contrast MRI data and DCE-MRI in 8 consecutive, angiographically-confirmed saccular cerebral aneurysms. We quantified contrast agent leakage rate (Ktrans) through the aneurysm wall using Tofts's model using a previously reported method. 1 Images were post-processed using in-house software to calculate hemodynamic parameters wall shear stress (WSS), 2 and permeability parameter Ktrans. Mean WSS and Ktrans were cross-sectionally compared across all aneurysms. We further used linear regression to compare hemodynamic and wall-permeability parameters. Results: We found no statistically significant correlation between mean WSS and Ktrans (R2=0.0012, p=0.93). Similarly there was no correlation between mean velocity and Ktrans (R2=0.020, p=0.73), as well as aneurysm diameter and Ktrans (R2=0.0050, p=0.87). Conclusion: In this study we did not find significant correlation between intra-aneurysmal hemodynamics and wall-permeability. Their lack of inter-correlation suggests they may contribute unique information about aneurysm risk profile and serve as independent markers of rupture risk. References: Vakil P, Ansari SA, Cantrell CG, et al . Quantifying intracranial aneurysm wall permeability for risk assessment using dynamic contrast-enhanced MRI: A pilot study. American Journal of Neuroradiology 2015;36:953–59. Schnell S, Ansari SA, Vakil P, et al . Three-dimensional hemodynamics in intracranial aneurysms: Influence of size and morphology. Journal of Magnetic Resonance Imaging 2014;39:120–131. Disclosures: M. Pan: None. P. Vakil: None. A. Vali: None. M. Markl: None. S. Schnell: None. S. Ansari: None.